2022
DOI: 10.3389/fbioe.2022.916229
|View full text |Cite
|
Sign up to set email alerts
|

Dynamic Culture of Mesenchymal Stromal/Stem Cell Spheroids and Secretion of Paracrine Factors

Abstract: In recent years, conditioned medium (CM) obtained from the culture of mesenchymal stromal/stem cells (MSCs) has been shown to effectively promote tissue repair and modulate the immune response in vitro and in different animal models, with potential for application in regenerative medicine. Using CM offers multiple advantages over the implantation of MSCs themselves: 1) simpler storage, transport, and preservation requirements, 2) avoidance of the inherent risks of cell transplantation, and 3) potential applica… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 20 publications
(8 citation statements)
references
References 184 publications
0
7
0
1
Order By: Relevance
“…3D culture of MSCs englobes a great variety of techniques, including but not limited to microcarriers, diverse scaffolds, microgels, and spheroids, which can be then cultured in bioreactors or other types of vessels. 3D culture better mimics the natural cell conditions, and increases the levels of secreted angiogenic and immunomodulatory factors ( 178 ).…”
Section: Msc Priming For Enhanced Immunomodulatory Potentialmentioning
confidence: 99%
“…3D culture of MSCs englobes a great variety of techniques, including but not limited to microcarriers, diverse scaffolds, microgels, and spheroids, which can be then cultured in bioreactors or other types of vessels. 3D culture better mimics the natural cell conditions, and increases the levels of secreted angiogenic and immunomodulatory factors ( 178 ).…”
Section: Msc Priming For Enhanced Immunomodulatory Potentialmentioning
confidence: 99%
“…Bioreactor-based 3D culture could enable large-scale production of SCs [ 136 ]. Furthermore, 3D culture enhances the immunomodulatory and angiogenesis ability of MSCs, strengthens their paracrine activity, and promotes the secretion of cytokines and growth factors [ 137 , 138 ]. 3D culture can alter the characteristics of SCs, and EVs are secreted by them, similarly, some studies have confirmed that 3D culture will have an effect on EVs.…”
Section: Current Applications Of Evs Derived From 3d Cultured Scsmentioning
confidence: 99%
“…Dynamic culture in bioreactors brings several advantages over static methods for the generation of spheroids, including a homogeneous environment, better diffusion of oxygen and nutrients, and longer periods of cultivation [ 48 , 49 ]. The stirred-tank bioreactor (STR) allows an easy and large-scale production of spheroids using culture modalities that allow the control of several parameters, including oxygen and pH [ 48 , 50 ]. Their main disadvantage is related to the relatively high shear forces that could have a detrimental effect on the spheroids’ shape and structure.…”
Section: 3d Spheroidsmentioning
confidence: 99%